Calcium-Dependent Protein Kinase CPK1 Controls Cell Death by In Vivo Phosphorylation of Senescence Master Regulator ORE1. Issue 5 (28th February 2020) - Durian, Guido; Sedaghatmehr, Mastoureh; Matallana-Ramirez, Lilian P.; Schilling, Silke M.; Schaepe, Sieke; Guerra, Tiziana; Herde, Marco; Witte, Claus-Peter; Mueller-Roeber, Bernd; Schulze, Waltraud X.; Balazadeh, Salma; Romeis, Tina
Abstract : The calcium-dependent protein kinase CPK1 regulates a pivotal developmental switch in senescence and leaf cell death through direct phosphorylation of transcription factor ORE1. Abstract: Calcium-regulated protein kinases are key components of intracellular signaling in plants that mediate rapid stress-induced responses to changes in the environment. To identify in vivo phosphorylation substrates of CALCIUM-DEPENDENT PROTEIN KINASE1 (CPK1), we analyzed the conditional expression of constitutively active CPK1 in conjunction with in vivo phosphoproteomics. We identified Arabidopsis ( Arabidopsis thaliana ) ORESARA1 (ORE1), the developmental master regulator of senescence, as a direct CPK1 phosphorylation substrate. CPK1 phosphorylates ORE1 at a hotspot within an intrinsically disordered region. This augments transcriptional activation by ORE1 of its downstream target gene BIFUNCTIONAL NUCLEASE1 ( BFN1 ). Plants that overexpress ORE1, but not an ORE1 variant lacking the CPK1 phosphorylation hotspot, promote early senescence. Furthermore, ORE1 is required for enhanced cell death induced by CPK1 signaling. Our data validate the use of conditional expression of an active enzyme combined with phosphoproteomics to decipher specific kinase target proteins of low abundance, of transient phosphorylation, or in yet-undescribed biological contexts. Here, we have identified that senescence is not just under molecular surveillance manifested by stringent gene regulatory control over ORE1 . In addition, the decision to die is superimposed by an additional layer of control toward ORE1 via its posttranslational modification linked to the calcium-regulatory network through CPK1.